Pregnancy Monitoring of In Vitro Produced Embryos in Buffaloes - Saliba, Wilson; Gimenes, Lindsay [UNESP]; Drumond, Roberti; Bayao, Henrique; Alvim, Mucio; Baruselli, Pietro; Bastianetto, Eduardo; Leite, Romulo; Gasparrini, Bianca (Int Buffalo Information Ctr, 2013)
In the present study, pregnancies obtained from 115 in vitro produced embryos were monitored by ultrasonography on days 30 and 60 after embryo transfer (ET), and at calving. Additionally, the health of newborns and recipients were also evaluated. On day 30 after ET, positive pregnancy was diagnosed in 50 animals (43.5%). A total of 8 fetal mortalities (16.0%) were verified from 30 days until calving, in which 2 occurred from 30 to 60 days after ET (4.0%), and 6 occurred from 60 days until calving (12.0%). In this last period of pregnancy, 3 pregnancy losses were due to abortion, and the other 3 were stillbirth. One additional animal was eliminated from the study, remaining 41 pregnancies. From these 41 pregnancies, a total of 20 female calves (48.8%) and 21 male calves (51.2%) were born. Pregnancies from female and male calves had a mean length of 309.8 and 310.9 days, respectively (range 300 to 328 days, and 297 to 320 days, respectively). Weight at calving was a mean of 31.4 and 33.8 kg for female and male calves, respectively. All calving occurred without intervention and dystocia was not observed in any case. No large offspring syndrome, hydramnios, hydroallantois, or umbilical cord anomalies were observed in calves. Delivery was normal in all recipients, and no puerperal infections, or retained placenta occurred. Suckling assistance was not necessary in any newborn. All genetic pedigree was confirmed later by DNA tests.
Keywords: Buffalos; IVP; ET; Calving